Synthesis and Characterization of Cual Batik Waste Dyes From Photocatalysis Using TiO2 From Ilmenite Bangka - Fuspita Istiqomah; Verry Andre Fabiani; Adisyahputra Adisyahputra (Stannum : Jurnal Sains dan Terapan Kimia, 2021)
Cual batik is one of the local products of the Bangka Belitung Islands. The expansion of cual batik in Bangka Belitung continues to increase, resulting in an increase in the production of cual batik cloth. Cual batik contains remasol dyes which are carcinogenic so that waste handling is appropriate and safe for the surrounding environment. One of them is using the TiO2 photocatalytic method from ilmenite Bangka. The results of XRF characterization showed that the TiO2 content after magnetic separator and HCl washing reached 69,975% and 77,260%. The results of XRD characterization showed that the optimal temperature of calcination was at 700ºC with the peak diffraction intensity of anatase TiO2 crystals at 2θ 48.9º, 53.53º and 53.92º. In FTIR characterization, there is a functional group spectrum of titanium dioxide (TiO2) at the absorption wave number 795 cm-1 showing Ti-O-Ti stretching vibrations, at wavenumber 2326 cm-1 showing Ti-O stretching vibrations. The results of photodegradation of cual batik waste showed a decrease in the dye content of remazol briliant blue when exposed to UV lamps and sunlight at contact times of 30, 60, and 90 minutes 85.21%, 82,75%, and 86,72% (UV light); 70,75%, 78,92%, and 93.51% (sunlight).